The sources of the personalistic concept of fertility - Horbowska, Justyna (Kwartalnik Naukowy Fides et Ratio, 2022)
Human fertility is a broad concept, encompassing the human biological, mental, and spiritual spheres. It can be referred to the procreation as the multiplication of the number of beings or it can be considered in the aspect of the human ontic structure, taking into account the ontic founds of the soul. Fertility was also understood as the ability to transmit life in the sense of the function of an organic body or a spiritual element. Finally, the issue of fertility was related to the mutual relations of parents and their children, and its understanding was broadened to include the context of transcendence. The purpose of this study is to reflect on the concept of human fertility that underlies the personalistic view of human fertility. In connection with this goal, the research problem was formulated in the form of the question: "What were the origins of the understanding of fertility of a person?" In the research work, the method of text analysis and the method of historicism was used. As a result of the study, it was possible to distinguish and outline the pre-philosophical approach to fertility, as well as ancient, medieval, modern, and contemporary concepts concerning fertility. Their review shows that human fertility was considered in the context of human sexuality. Moreover, the materialistic concepts related to the monistic vision of man were accompanied by the understanding of fertility as the ability to procreate, while the dualistic concepts, assuming the presence of the spiritual element, attributed to it the ability to animate the material body. The hylomorphic concept of the human structure, proper to the philosophy of St. Thomas Aquinas and supplemented with a reference to individual existence was presented in the context of the approach to Aristotle's understanding of the soul, along with his discussion of human procreation as a special case of animal reproduction, and then supplemented with a personal context in the contemporary sense. An attempt was made to answer the research question, but the issue was not discussed exhaustively, which leaves room for further research.